2019
DOI: 10.1108/ijoa-10-2017-1262
|View full text |Cite
|
Sign up to set email alerts
|

Psychological identification with job: a leadership-OCB mediator

Abstract: Purpose This study aims to examine influence of transformational and transactional leadership styles on employees’ organisational citizenship behaviours (OCBs), as well as the mediating role of job involvement in the Ghanaian hospitality industry. Design/methodology/approach Data were gathered from 258 employees in some selected hotels and restaurants in the Greater Accra Region of Ghana through a survey and analysed using covariance-based structural equation modelling. Findings The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 57 publications
(138 reference statements)
3
13
0
Order By: Relevance
“…There is an inconsistency in the results of the previous studies between TAL and OCBs. For example, Ali et al, 2014;Dartey-Baah and Addo, 2019;and Nguni et al, 2006, reported that TAL has a positive and significant impact on OCBs. On the other hand, studies conducted by Abu Nasra and Arar (2020); Arar and Abu Nasra (2019); TAL has a non-significant effect on OCBs among teachers.…”
Section: Tfl Tal and Ocbsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is an inconsistency in the results of the previous studies between TAL and OCBs. For example, Ali et al, 2014;Dartey-Baah and Addo, 2019;and Nguni et al, 2006, reported that TAL has a positive and significant impact on OCBs. On the other hand, studies conducted by Abu Nasra and Arar (2020); Arar and Abu Nasra (2019); TAL has a non-significant effect on OCBs among teachers.…”
Section: Tfl Tal and Ocbsmentioning
confidence: 99%
“…Leaders following TFLs would inspire the confidence, loyalty, and respect of dependents and motivate them to participate in organizationfriendly conduct that exceeds expectations (Bass, 1985); in contrast, TAL leaders are subject to pre-determined targets based on rewards and contingent incentive strategies and outstanding management (Bass and Avolio, 1990;. Both leadership styles TFL and TAL have been confirmed significantly correlated and impact on OCBs (Dartey-Baah and Addo, 2019;. Several prior studies investigated and examined both styles of leadership, TFL and TAL, in the school context (Ali et al, 2014;Nahum-Shani and Somech, 2011;Nguni et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance; research that has explored task leader conduct (i.e., transactional leadership, contingent reward, initiating structure) conveyed that effective leaders can illustrate certain roles, resolve issues, and coordinate maneuvers (Bass, 1985; Burns, 1978; Karam et al, 2019; Podsakoff et al, 2006; Yukl, 2012). Positive effects of leaders on employee attitudes and behaviors have been established in the relevant literature (e.g., Dartey-Baah & Addo, 2019; Gardner et al, 2010). The current research looks into transactional leadership and its influence within an organizational perspective.…”
Section: Introductionmentioning
confidence: 99%